NOTE ON WILD BEES OF THE MAGELLAN REGION, CHILE (HYMENOPTERA: APOIDEA) (Acta Entomológica Chilena, 2022)
Some new records of bees, geographical distribuiion, and variation of sume characiers are presentedhere.
Keywords: wild bees, Magelian Región, Chile